Media Pembelajaran Sejarah Proklamasi Indonesia Berbasis Macromedia Flash di Kelas VI Sekolah Dasar - Lilis Mistina; Eddy Noviana; Mahmud Alpusari (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This study aims to develop appropriate and practical learning media for the history of the proclamation of Indonesia based on macromedia flash. This research is research & development with four D (4-D) models: Define, Design, Develop, and Dissemination. The research subjects were 3 teachers and 15 grade VI students at SDN 164 Pekanbaru and it was conducted in the odd semester of 2021/2022. Data collection techniques and instruments were in the form of expert validation questionnaire sheets and teacher and student response questionnaire sheets. Data analysis techniques with statistical calculations in the form of media feasibility test scores and practicality tests for teacher and student responses using a Likert scale. The results of the product and material validation showed a score of 87.45% (very feasible) and the results of the practicality test showed a score of 90% (very practical). Thus, it is concluded that the learning media developed by the researcher is very feasible and very practical.